Hot Integrals

Calculus Level 5

A 0 1 ln ( x ) ln ( 1 x ) x d x = B arctan ( e x ) arctan ( e x ) d x A\int_0^1\dfrac{\ln(x)\ln(1-x)}{x}\,dx=B\int_{-\infty}^{\infty}\arctan(e^x)\arctan(e^{-x})\,dx

The equation above holds true for positive coprime integers A A and B B . Find A + B A+B .


The answer is 11.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Jun 30, 2019

The first integral is easy: 0 1 ln x ln ( 1 x ) x d x = n 1 1 n 0 1 ln x x n 1 d x = n 1 1 n 3 = ζ ( 3 ) \int_0^1 \frac{\ln x \ln(1-x)}{x}\,dx \; = \; -\sum_{n\ge 1}\frac{1}{n}\int_0^1 \ln x x^{n-1}\,dx \; = \; \sum_{n\ge1} \frac{1}{n^3} \; =\; \zeta(3) A double integration by parts shows that 0 π u ( π u ) e ( 2 k + 1 ) u i d u = 4 i ( 2 k + 1 ) 3 k N { 0 } \int_0^\pi u(\pi-u)e^{-(2k+1)ui}\,du \; = \; -\frac{4i}{(2k+1)^3} \hspace{2cm} k \in \mathbb{N}\cup\{0\} Thus 0 π u ( π u ) sin u ( 1 e 2 K u i ) d u = 2 i k = 0 K 1 0 π u ( π u ) e ( 2 k + 1 ) u i d u = 8 k = 0 K 1 1 ( 2 k + 1 ) 3 \int_0^\pi \frac{u(\pi-u)}{\sin u}\big(1 - e^{-2Kui}\big)\,du \; = \; 2i\sum_{k=0}^{K-1}\int_0^\pi u(\pi-u)e^{-(2k+1)ui}\,du \; = \; 8\sum_{k=0}^{K-1}\frac{1}{(2k+1)^3} for all K 0 K \ge 0 , and since u ( π u ) sin u \frac{u(\pi-u)}{\sin u} is Lebesgue integrable over ( 0 , π ) (0,\pi) , we deduce, on letting K K \to \infty , that 0 π u ( π u ) sin u d u = 8 k 0 1 ( 2 k + 1 ) 3 = 8 ( 1 1 8 ) ζ ( 3 ) = 7 ζ ( 3 ) \int_0^\pi \frac{u(\pi-u)}{\sin u}\,du \; = \; 8\sum_{k \ge 0}\frac{1}{(2k+1)^3} \; = \; 8\left(1-\tfrac18\right)\zeta(3) \; = \; 7\zeta(3) Then the successive substitutions y = e x y = e^x , y = tan t y = \tan t , u = 2 t u = 2t give tan 1 ( e t ) tan 1 ( e t ) d t = 0 tan 1 ( y ) tan 1 ( y 1 ) y d y = 0 1 2 π t ( 1 2 π t ) sin t cos t d t = 1 4 0 π u ( π u ) sin u d u = 7 4 ζ ( 3 ) \begin{aligned} \int_{-\infty}^\infty \tan^{-1}(e^t)\tan^{-1}(e^{-t})\,dt & =\; \int_0^\infty \frac{\tan^{-1}(y) \tan^{-1}(y^{-1})}{y}\,dy \; = \; \int_0^{\frac12\pi}\frac{t(\frac12\pi-t)}{\sin t \cos t}\,dt \\ & = \; \frac14\int_0^\pi \frac{u(\pi-u)}{\sin u}\,du \; = \; \tfrac74\zeta(3) \end{aligned} so we deduce that A = 7 A=7 , B = 4 B=4 , and hence A + B = 11 A+B = \boxed{11} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...